Misi Dalam Kaitannya Dengan Pemikiran Martin Buber - Franciscus Hardjosetiko (Sekolah Tinggi Widya Sasana, 2020)
Mission focuses on the relationship between humans. Therefore, Christian anthropology becomes a supporter of the church's mission. In this study Martin Buber's thought could be one of the inspirational materials of the Church's mission. His background of thinking fits perfectly with the theme of the seminar. Martin Buber's background is at odds with his idea of how one should relate to others.